2012
DOI: 10.1063/1.3673863
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric performance of Zn-substituted type-VIII clathrate Ba8Ga16Sn30 single crystals

Abstract: We have grown single-crystalline samples of Zn-substituted type-VIII clathrate Ba 8 Ga 16 Sn 30 with n-type carriers by Sn-flux method. The actual compositions of the single crystals were found to be described as Ba 8 Ga 15.8À2y Zn y Sn 30.2þy (y ¼ 0 $ 0.54), where the charge balance is well maintained. As y goes from 0 to 0.42, the resistivity at 300 K decreases from 5.3 to 3.0 mX cm gradually, but the effective mass is essentially constant at 1.2 $ 1.5m 0 , indicating intact band structure near the conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…The ZT values for the n-type BGS were enhanced by partial substitution of Al or Zn for Ga in the framework [16,[19][20][21]. Especially, the ZT value of the Al substituted BGS was enhanced up to 1.2 at 500 K. Furthermore, doping with Cu in Ba 8 Ga 16Àx Cu x Sn 30 at a very low level x of 0.033 led to the highest ZT of 1.35 among the n-type substituted BGS samples [21].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The ZT values for the n-type BGS were enhanced by partial substitution of Al or Zn for Ga in the framework [16,[19][20][21]. Especially, the ZT value of the Al substituted BGS was enhanced up to 1.2 at 500 K. Furthermore, doping with Cu in Ba 8 Ga 16Àx Cu x Sn 30 at a very low level x of 0.033 led to the highest ZT of 1.35 among the n-type substituted BGS samples [21].…”
Section: Introductionmentioning
confidence: 77%
“…It was attributed to the increase of the carrier mobility and suppression of the pronounced increase in j (T > 450 K), which arises from the bipolar effect. The ZT value has a maximum value of 1.35 at 540 K. The substitution of Sb for Sn in p-type BGS, however, caused no improvement in ZT, the maximum of which stayed around 1.0 at 480 K [15,16,20].…”
Section: Introductionmentioning
confidence: 81%
“…23 By assuming that the lattice contribution Κ L becomes constant above 615 K and that the bipolar contribution Κ b can be neglected below 615 K, 18 the two contributions can be estimated as shown in Figure 7 (b). The bipolar contribution Κ b is typically very small below the intrinsic conduction region of materials.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Figure shows a typical photo of the grown crystal sample with Zn content x = 1. The obtained sample exhibited 5mm size, and it is as large as that of Zn substituted samples grown by β ‐Sn flux method …”
Section: Resultsmentioning
confidence: 91%
“…For the quaternary Sn‐based type‐VIII clathrates Ba‐Ga‐Sn‐X(X = Cu, Al, Ge), the dimensionless figure of merit ZT is enhanced significantly; For example, the ZT of Cu‐doped Ba 8 Ga 16 Sn 30 with n ‐type carriers using Sn‐flux method is 1.35 at 540K . Recently, it was found that the ZT of single crystalline n ‐type Ba 8 Ga 16 Sn 30 sample via white Sn‐flux method was enhanced by Zn substitution . In general, the quaternary Sn‐based clathrates Ba‐Ga‐Sn‐X were prepared by the method of Sn‐flux, Ga‐flux, and double‐flux of Ga and Sn.…”
Section: Introductionmentioning
confidence: 99%